2002
DOI: 10.1046/j.1529-8817.2002.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

CARRAGEENANS BIOSYNTHESIZED BY CARPOSPOROPHYTES OF RED SEAWEEDS GIGARTINA SKOTTSBERGII (GIGARTINACEAE) AND GYMNOGONGRUS TORULOSUS (PHYLLOPHORACEAE)1

Abstract: Carrageenans biosynthesized by gametophytic and tetrasporic plants of seaweeds belonging to the Gigartinaceae and Phyllophoraceae are different: gametophytes produce carrageenans of the kappa family, whereas lambda‐carrageenans are extracted from tetrasporophytes. For Gigartina skottsbergii Setchell and Gardner and Gymnogongrus torulosus Hooker et Harvey, mature cystocarps were isolated and carrageenans were extracted. Structural determination by methylation analysis, Fourier transform infrared spectroscopy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
2
8
1
1
Order By: Relevance
“…Specifically, the aims of this study were, using FT‐IR microspectroscopy, to (1) corroborate evidence from previous studies (McCandless et al. 1983, Estevez et al. 2002) of the presence of κ‐carrageenan in gametophytes and carposporophytes, and λ‐carrageenan in tetrasporophytes of C. verrucosus ; (2) assess whether individual carpospores and tetraspores of C. verrucosus could be reliably discriminated based on FT‐IR microspectroscopy; and (3) assess the effect of different types of data pretreatment on the accuracy of classification of spore types (Heraud et al.…”
Section: Band Assignment For Fourier Transform Infrared (Ft‐ir) Specmentioning
confidence: 59%
See 2 more Smart Citations
“…Specifically, the aims of this study were, using FT‐IR microspectroscopy, to (1) corroborate evidence from previous studies (McCandless et al. 1983, Estevez et al. 2002) of the presence of κ‐carrageenan in gametophytes and carposporophytes, and λ‐carrageenan in tetrasporophytes of C. verrucosus ; (2) assess whether individual carpospores and tetraspores of C. verrucosus could be reliably discriminated based on FT‐IR microspectroscopy; and (3) assess the effect of different types of data pretreatment on the accuracy of classification of spore types (Heraud et al.…”
Section: Band Assignment For Fourier Transform Infrared (Ft‐ir) Specmentioning
confidence: 59%
“…They also implied that this relationship should hold for diploid carpospores and haploid tetraspores (Gordon‐Mills and McCandless 1975). However, Estevez et al. (2002), using FT‐IR spectroscopy and 13 C‐nuclear magnetic resonance ( 13 C‐NMR) spectroscopy on carposporophytes of Gigartina skottsbergii (Gigartinaceae) separated from the gametophytic pericarp tissue, clearly demonstrated that the diploid carposporophytes contained κ‐ and ι‐carrageenans like the haploid gametophytes.…”
Section: Band Assignment For Fourier Transform Infrared (Ft‐ir) Specmentioning
confidence: 99%
See 1 more Smart Citation
“…As concentrações de Cr (3,0µg.g -1 ), Cu (4,1µg.g -1 ), Fe (1087µg.g -1 ), Mn (243,5µg.g -1 ) e Zn (32µg.g -1 ) em Gymnogongrus sp foram em média, maiores que em Ulva fasciata (0,9µg.g -1 ; 2,9µg.g -1 ; 394µg.g -1 ; 9,9µg.g -1 ; 6,4µg.g -1 respectivamente para Cr, Cu, Fe, Mn e Zn). Segundo Estevez et al (2002) algas vermelhas, como as do gênero Gymnogongrus, possuem grupos polissacarídicos, como as carragenanas, ligados à parede celular do vegetal. Wahbeh (1985) cita que estes compostos possuem elevada afinidade por elementos metálicos em função de suas cargas e pela estabilidade de suas ligações com metais pesados.…”
Section: Discussionunclassified
“…The list of studied species includes C. crispus, Gigartina alveata, G. clavifera, G. decipiens, G. pistillata, G. skottsbergii, Gymnogongrus torulosus, S. crispata, S. atropurpurea and several commercial and underutilised species collected from the occidental Portuguese coast. 8,[10][11][12][16][17][18][19][20][21][22][23][24] Although the functional properties in dairy applications have been studied for j/i-hybrids extracted from specific species, no systematic analysis of the j/i-hybrids has been reported. Most of the studies mentioned above started from a certain seaweed species and studied the functional properties of the carrageenans extracted.…”
Section: Introductionmentioning
confidence: 98%